Performance of pulsed plasma thrusters - Loh, Kelvin Kwong Lam. (2009)
A pulsed plasma thruster (PPT) is a type of electromagnetic propulsion system which uses plasma as the working fluid to electromagnetically accelerate the fluid to high exhaust velocities. The PPT is primarily designed for long duration satellite missions for attitude control as well as interplanetary and deep space missions. The auto-initiated PPT is one variant of the PPTs developed. This work is a numerical work on the performance of an auto-initiated pulsed plasma thruster. The goal is to compare with the experimental results obtained from the work done at the Indian Institute of Technology, Kanpur. The plasma acceleration phase is modeled by a simple 1-D analytical model, as well as a set of integro-differential equations from the slug, and snowplow model. The different modes of EM acceleration for plasma (steady, and unsteady) is also explored. The case study of Hartmann flows that is investigated is a case for steady plasma acceleration flows. The results provide an understanding that ideal magnetohydrodynamic (MHD) models for steady electromagnetic accelerations do not need to solve for the magnetic induction equation in Maxwell's equations, which results in a significant simplification in the equations that needs to be solved for the 1-D case. As for the unsteady case, the analytical, slug, and snowplow models are developed and the results compared against the experimental data. The results show that the slug model relates the best amongst the three models to the experimental data within 20% of the impulse bit at pressure levels greater than 5 mbar. This suggests that the auto-initiation PPT operates using a slug mode of operation. This also shows that the slug model can be a very useful tool for the conceptual design phase of a solid ablation PPT. This work can be further improved by coupling the resistive MHD equations with the external circuit equations to include resistive effects in the plasma sheet.